2019
DOI: 10.1186/s13049-019-0658-7
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital cardiopulmonary resuscitation duration and neurological outcome after out-of-hospital cardiac arrest among children by location of arrest: a Nationwide cohort study

Abstract: Background Little is known about the associations between the duration of prehospital cardiopulmonary resuscitation (CPR) by emergency medical services (EMS) and outcomes among paediatric patients with out-of-hospital cardiac arrests (OHCAs). We investigated these associations and the optimal prehospital EMS CPR duration by the location of arrests. Methods We included paediatric patients aged 0–17 years with OHCAs before EMS arrival who were transported to medical insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…20 As a result, CPR education and widespread AED installation have occurred, resulting in a higher proportion of bystander interventions. 21 The present study suggests that schoolchildren could contribute to improving outcomes in OHCA. Therefore, adding BLS training in school curricula is beneficial and should be valued in school education.…”
Section: Clinical Implicationmentioning
confidence: 59%
See 1 more Smart Citation
“…20 As a result, CPR education and widespread AED installation have occurred, resulting in a higher proportion of bystander interventions. 21 The present study suggests that schoolchildren could contribute to improving outcomes in OHCA. Therefore, adding BLS training in school curricula is beneficial and should be valued in school education.…”
Section: Clinical Implicationmentioning
confidence: 59%
“…A study in Denmark has reported that educating schoolchildren on CPR is associated with an increase in lay CPR rates and survival following OHCA; the survival rate of OHCA has increased significantly since BLS education became mandatory for schoolchildren 19 . In 2015, the Japan Circulation Society published the statement “Aiming for Zero Deaths: Prevention of Sudden Cardiac Death in Schools and Sport Locations.” 20 As a result, CPR education and widespread AED installation have occurred, resulting in a higher proportion of bystander interventions 21 . The present study suggests that schoolchildren could contribute to improving outcomes in OHCA.…”
Section: Discussionmentioning
confidence: 77%
“…6,7 Some studies from case report and case series showed that prolonged CPR, especially in combination with the utility of extracorporeal membrane oxygenation has meaningful survival rates and the survivors are able to regain favorable neurological outcome and return to normal life. [8][9][10][11][12] However, successful recovery after extremely long CPR with manual chest compressions, as in our case, has rarely been reported. 8,13 Our case suggested that prolonged resuscitation is not futile although it poses a real challenge for doctors with uncertain outcomes.…”
mentioning
confidence: 63%
“…Finally, prehospital information did not include in this database. Although the associations between prehospital interventions and postresuscitation heart functions had not been clearly addressed, some previous studies pointed out that bystander CPR, public defibrillation were strong predictors of survival (even good neurologic outcome) [37,38].…”
Section: Discussionmentioning
confidence: 99%